A Study on Perception of Farmers towards the Impact of Cloud Based Services on Agricultural Sector - Naik Dipan M; Dr. Bhawesh Kumawat (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid advancement of digital technology has significantly transformed the agricultural sector, with cloud-based services emerging as a crucial tool for enhancing farming efficiency and productivity. This study explores the perception of farmers towards the impact of cloud-based services on agriculture, focusing on their awareness, accessibility, benefits, market linkages, and financial feasibility. The research examines how socio-demographic factors such as age, education, gender, and income levels influence farmers’ adoption and utilization of these digital solutions. A structured survey was conducted among farmers in Gujarat State, and data analysis was performed using descriptive statistics and chi-square tests to determine significant differences in perceptions. The findings reveal that awareness and knowledge of cloud-based services vary significantly based on education, gender, and income levels, with younger, educated, and higher-income farmers showing greater familiarity. While accessibility to digital infrastructure remains consistent across demographics, perceptions of productivity benefits, market linkages, and financial feasibility differ significantly among socio-demographic groups. The study highlights the potential of cloud-based services in improving decision-making, market access, and overall farm productivity but also identifies key challenges, including limited affordability, digital literacy gaps, and gender disparities in adoption. The research underscores the need for targeted government initiatives, training programs, and financial support to ensure widespread and equitable adoption of cloud-based agricultural solutions. These findings provide valuable insights for policymakers, agritech firms, and agricultural institutions in designing effective digital interventions to support sustainable farming in Gujarat State and beyond.